Effect of hysteresis properties of shape memory alloy-tuned mass damper on seismic control of power transmission tower. Issue 4 (March 2019) - Tian, Li; Gao, Guodong; Qiu, Canxing; Rong, Kunjie
Statistics from past strong earthquakes revealed that electricity transmission towers were vulnerable to earthquake excitations. It is necessary to mitigate the seismic responses of power transmission towers to ensure the safety of such structures. In this research, a novel shape memory alloy-tuned mass damper is proposed, and seismic vibration control of power transmission tower using shape memory alloy-tuned mass damper based on three types of shape memory alloy materials (i.e. NiTi, M-CuAlBe, P-CuAlBe) is analyzed. The detailed three-dimensional finite element model of a power transmission tower incorporated with shape memory alloy-tuned mass damper is developed using numerical simulation software ANSYS. The control effects of shape memory alloy-tuned mass damper on the seismic vibration of power transmission tower are assessed using nonlinear time history analysis method. The interested seismic performance indices include displacement, acceleration, and base shear force. In addition to the shape memory alloy materials, the influence of seismic intensity and frequency ratio are conducted for the optimal design. It is shown that installing shape memory alloy-tuned mass damper well reduced the seismic responses of power transmission tower. The comparison between different shape memory alloys indicated that the damping of the shape memory alloy-tuned mass damper is beneficial to mitigate the vibrations.